Group sex, suicidality and online partners: implications for HIV and suicide prevention: a short report. Issue 8 (2nd August 2020) - Kongjareon, Yamol; Samoh, Nattharat; Lim, Sin How; Peerawaranun, Pimnara; Jonas, Kai J.; Guadamuz, Thomas E.
ABSTRACT: HIV-related factors and suicide-risk status were assessed among YMSM aged 18–24 years recruited through various MSM-related online social apps in Bangkok ( N = 1394). The online survey assessed demographic characteristics, sexual behaviours and suicide-risk status. Measure of suicide risk was taken from the Suicidal Behaviors Questionnaire-Revised (cut-off score of seven or higher). Among participants, 249 (17.9%) reported suicide-risk. In multivariable logistic regression, correlates of suicide-risk status included having sometimes or often ever participated in group sex (AOR=1.58, 95% CI: 1.17–2.14), having received money or opportunities for sex (AOR=1.54, 95% CI: 1.09–2.17), often seeking partners online (AOR=1.59, 95% CI: 1.05–2.39), inconsistent condom use (AOR=1.67, 95% CI: 1.26–2.21), and self-assessed as having "medium" or "high" HIV risk (AOR=2.53, 95% CI: 1.61–3.98 and AOR=3.35, 95% CI: 1.92–5.82, respectively). Findings suggest that HIV risk behaviours shown by YMSM are significantly associated with higher risk of suicide.